FIRST RECORD OF MYOTIS FORMOSUS HODGSON'S BAT (HODGSON, 1835) FROM BAJAUR AGENCY, PAKISTAN - Hamidullah; A. Javid; S. B. Rasheed; J. Zeb; A. Ullah; M. I. Khan; Attaullah (Journal of Animal and Plant Sciences, 2018)
During a two year survey extending from 2014 through 2016, specimens ( n = 3) of Hodgson's bat Myotis formosus were captured from Bajaur Agency, FATA in Pakistan using mist and hand nets. External body, cranial and bacular features of the captured specimens were recorded and compared with available literature. Mean head and body length of the captured specimens was 42.06±4.01 mm, forearm length was 47.16±0.93 mm, greatest length of skull (n = 2) was 17.38±0.17 mm while total baculum length (n = 1) was 8.1 mm. The species is the first record from the study area. Bat populations are declining in their natural
Keywords: Hodgson's bat; FATA; Forearm; Baculum; Skull.